1994
DOI: 10.1084/jem.179.5.1653
|View full text |Cite
|
Sign up to set email alerts
|

Gene structure of the Helicobacter pylori cytotoxin and evidence of its key role in gastric disease.

Abstract: The gram negative, microaerophilic bacterium Helicobacter I~Iori colonizes the human gastric mucosa and establishes a chronic infection that is tightly associated with atrophic gastritis, peptic ulcer, and gastric carcinoma. Cloning of the H. pylori cytotoxin gene shows that the protein is synthesized as a 140-kD precursor that is processed to a 94-kD fully active toxin. Oral administration to mice of the purified 94-kD protein caused ulceration and gastric lesions that bear some similarities to the pathology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
514
3
7

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 567 publications
(540 citation statements)
references
References 22 publications
16
514
3
7
Order By: Relevance
“…The reason gastric T cells of MALT lymphoma, while delivering full help to B cells, are apparently deficient in 2 mechanisms involved in the concomitant control of B-cell growth remains unclear. It has been shown that VacA toxin released by H. pylori strains harboring a pathogenicity island 32 inhibits antigen processing in APCs but not the exocytosis of perforin-containing granules of natural killer cells. 33 It is possible that, in some H. pylori-infected individuals, other bacterial components affect the development or expression of regulatory cytotoxic mechanisms on B-cell proliferation by gastric T cells, allowing exhaustive and unbalanced B-cell help and lymphomagenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The reason gastric T cells of MALT lymphoma, while delivering full help to B cells, are apparently deficient in 2 mechanisms involved in the concomitant control of B-cell growth remains unclear. It has been shown that VacA toxin released by H. pylori strains harboring a pathogenicity island 32 inhibits antigen processing in APCs but not the exocytosis of perforin-containing granules of natural killer cells. 33 It is possible that, in some H. pylori-infected individuals, other bacterial components affect the development or expression of regulatory cytotoxic mechanisms on B-cell proliferation by gastric T cells, allowing exhaustive and unbalanced B-cell help and lymphomagenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we were able to detect a specific 58-kDa antigen in H. pylori lysate and in serum samples from H. pylori-infected individuals. The molecular mass of the serum antigen is analogous to the 58-kDa fragment of the 87-kDa cytotoxin domain of the VacA protein (8,23,27), the subunit cellular antigen (59 kDa) of the native H. pylori catalase (26), and the H. pylori catalase gene product (20). However, further investigation of the structure of the target H. pylori serum antigen will be performed.…”
Section: Immunodiagnosis Of H Pylori Infection Is Attractive In Com-mentioning
confidence: 99%
“…The mature monomer could be cleaved proteolytically into two fragments: an N-terminal 34 kDa fragment and a C-terminal 58 kDa fragment that remain associated after cleavage. 71 The ability to induce vacuoles is localized mostly but not entirely in the first fragment, whereas the second fragment is mostly involved in cell targeting.…”
Section: Relevance Of Strain Types Of H Pylori In the Outcome Of Infmentioning
confidence: 99%
“…102 I strains promote gastric damage similar to that observed in humans. 71,104 To date, studies have shown that CagA is one of the proteins produced by the pathogenicity island (cag PAI). Recent studies using isogenic mutants strains lacking the cagA gene have shown that IL-8 induction may not be directly due to CagA protein but to the products of cag PAI genes.…”
Section: Relevance Of Strain Types Of H Pylori In the Outcome Of Infmentioning
confidence: 99%